Case Report: Successful retrieval of a migrated left atrial appendage occluder through the synergistic use of a guidewire and a gooseneck snare - Bao, Yue; Yi, Hongwei; Ma, Jun; Han, Hongwei (Frontiers in Cardiovascular Medicine, 2024)
Left atrial appendage occluder (LAAO) dislodgement with embolization is a rare occurrence. If the LAAO migrates into the left atrium or ventricle, it can lead to acute heart failure or even death in a person, necessitating urgent surgical intervention. Currently, most cases of LAAO dislodgement are managed through open-heart surgery, while percutaneous retrieval of the LAAO has been reported only in a few cases with limited associated experience. This article reports a case of a patient in whom a migrated LACbes device was successfully retrieved using a catheter-based approach, demonstrating an innovative and minimally invasive treatment strategy.